The wedding guest [compact disc, unabridged] : an Alex Delaware novel - Kellerman, Jonathan (Kellerman, Jonathan. Alex Delaware novels, 2019)
When LAPD Lieutenant Milo Sturgis needs to get into the mind of a killer, he leans on the expertise of his best friend, psychologist Dr. Alex Delaware. Delaware and Sturgis find themselves crashing a wild Saints and Sinners-themed wedding reception. A horrified bridesmaid has discovered the body of a young woman, dressed to impress in pricey haute couture and accessorized with a grisly red slash around her neck. The party's over, and the hunt for whoever killed it is on.